2021
DOI: 10.1093/rheumatology/keab700
|View full text |Cite
|
Sign up to set email alerts
|

Consumer-based activity trackers in evaluation of physical activity in myositis patients

Abstract: Objectives Inflammatory myopathies are characterized by muscle weakness that limit activities of daily living. Daily step count is an accepted metric of physical activity. Wearable technologies such as Fitbit® enable tracking of daily step counts. We assessed psychometric properties of Fitbit® and compared the accuracy of Fitbit® step counts to ActiGraph®. Methods This was a pilot, proof of concept, prospective observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
1
8
0
2
Order By: Relevance
“…[35][36][37] to strong positive between habitual physical activity levels measured by accelerometers and longitudinal changes in clinical outcomes for patients with myositis, as improvements in the habitual physical activity levels coincided with improvements in MMT8, HAQ, and PhGD. 24,38,39 Self-perceived physical function assessed by HAQ appeared to be among the most influential factors (strongest predictors) on physical quality of life in the present study. Similar findings have been observed previously 40 and reaffirm that HAQ is a vital measure in the monitoring of patients with myositis.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…[35][36][37] to strong positive between habitual physical activity levels measured by accelerometers and longitudinal changes in clinical outcomes for patients with myositis, as improvements in the habitual physical activity levels coincided with improvements in MMT8, HAQ, and PhGD. 24,38,39 Self-perceived physical function assessed by HAQ appeared to be among the most influential factors (strongest predictors) on physical quality of life in the present study. Similar findings have been observed previously 40 and reaffirm that HAQ is a vital measure in the monitoring of patients with myositis.…”
Section: Discussionsupporting
confidence: 44%
“…Both subjectively (IPAQ) and objectively (accelerometery) physical activity was unrelated to physical and mental quality of life, suggesting that high or low levels of physical activity may not per se be sensitive factors in the monitoring of patients with stable myositis in relation to concurrent assessments/interventions on quality of life. However, some studies have observed moderate to strong positive between habitual physical activity levels measured by accelerometers and longitudinal changes in clinical outcomes for patients with myositis, as improvements in the habitual physical activity levels coincided with improvements in MMT8, HAQ, and PhGD 24,38,39 …”
Section: Discussionmentioning
confidence: 99%
“… 22 Most studies across the subgroups of IIM found that CK levels do not correlate with muscular function. 23 26 …”
Section: Discussionmentioning
confidence: 99%
“…Ein Zusammenhang zwischen der Muskelkraft und dem Aktivitätsprofil konnte jedoch nicht nachgewiesen werden [ 30 ]. Eine prospektive Beobachtungsstudie mit 24 Patient:innen mit inflammatorischen Myopathien konnte eine Korrelation der täglichen Schrittzahl sowie maximalen 1‑min-Schrittfrequenz mit der Einschätzung der Krankheitsaktivität durch Arzt und Patient, dem HAQ-Behinderungsindex, SF-36 PF10 sowie verschiedenen Funktionstests (6-min-Gehtest, Timed up-and-go, Sit-to-Stand-Test) zeigen [ 31 ].…”
Section: Krankheitsmonitorierungunclassified